Does IFRIC 15 Matter? The Decision Usefulness of Accelerated Revenue and Earnings Recognition - Lau Chee Kwong, (Asian Academy of Management Journal of Accounting and Finance, 2013)
The newly issued IFRIC 15 Agreements for the Construction of Real Estate are likely to cause Malaysian property developers to change their revenue recognition policy from a stage-of-completion basis (accelerated) to a completion basis (conservative). In the US, consistent with the approach taken by the Financial Accounting Standards Board (FASB), Altomuro, Beatty and Weber (2005) found that reported earnings based on accelerated revenue recognition are value relevant. The subsequent elimination of this industry practice in the US by the Securities and Exchange Commission (SEC) has indeed caused a decline in earnings informativeness. In contrast, this study finds that reported earnings based on the existing accelerated revenue recognition policy are weak and are no better than operating cash flow in predicting the stock returns, market pricing and future operating cash flows of Malaysian property developers. At the same time, the planned new, more conservative revenue recognition policy based on a completion basis may not improve the decision usefulness of financial reporting among property developers, at least not in the short run. Rather, this shift in revenue recognition policy is expected to decrease accrual-based earnings management opportunities, and managers may begin to focus on managing real activities instead (Cohen, Dey, & Lys, 2008).